How Can We Engage Oncology Care Providers and Glioblastoma Patients in Conversations About Physical Activity: A Qualitative Descriptive Study Using the Theoretical Domains Framework - Jodi E. Langley; Grace Warner; Christine Cassidy; Robin Urquhart; Mary MacNeil; Melanie R. Keats (Current Oncology)
Glioblastoma (GB) is the most common primary malignant brain tumour in adults. Physical activity (PA) has value as a supportive service for individuals living with a GB diagnosis to help maintain quality of life and physical functioning. The objective of this study is to understand how oncology care providers (OCPs), family/friend caregivers, and health system decision makers can include conversations of PA into care for those living with a GB. We conducted 19 semi-structured interviews guided by the Capability, Opportunity, Motivation–Behaviour (COM-B) model and further refined them by the theoretical domains framework (TDF). The data were then analyzed using a directed content analysis using a codebook generated using the TDF. Patients and family/friend caregivers appreciated hearing about PA from their OCPs, from initial diagnosis into follow-up appointments, and they saw PA as a way to take a break from cancer/medically focused care, and historical PA behaviours did not mean patients were more or less likely to be open about PA discussions. This study further emphasises the inclusion of PA discussions in clinical care. OCPs in GB care feel they have the knowledge to partake in PA conversations, and GB patients are open to having these conversations. However, specific barriers are in place that do not lead to widespread implementation of PA discussions for all patients.